2022
DOI: 10.1093/infdis/jiac167
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Duration After Infection From SARS-CoV-2 in the Texas Coronavirus Antibody Response Survey

Abstract: Understanding the duration of antibodies to the SARS-CoV-2 virus that causes COVID-19 is important to controlling the current pandemic. Participants from the Texas Coronavirus Antibody REsponse Survey (Texas CARES) with at least one nucleocapsid protein antibody test were selected for a longitudinal analysis of antibody duration. A linear mixed model was fit to data from participants (n= 4,553) with one to three antibody tests over 11 months (10/1/2020-9/16/2021), and models fit showed that expected antibody r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
7
22
0
Order By: Relevance
“…6,7 In contrast, the infection seroprevalence is fairly stable over the sampling period, consistent with IgG antibody remaining detectable for months after infection. 8 This estimate of infection prevalence is comparable to CDC-reported laboratory surveillance estimates for Georgia during the study period (Table 1). 9 A household-based survey from August to December 2020 estimated a seroprevalence of 7.8% (95% CI, 5.1-11.7) in the core Atlanta counties of Fulton and DeKalb.…”
Section: Discussionsupporting
confidence: 76%
“…6,7 In contrast, the infection seroprevalence is fairly stable over the sampling period, consistent with IgG antibody remaining detectable for months after infection. 8 This estimate of infection prevalence is comparable to CDC-reported laboratory surveillance estimates for Georgia during the study period (Table 1). 9 A household-based survey from August to December 2020 estimated a seroprevalence of 7.8% (95% CI, 5.1-11.7) in the core Atlanta counties of Fulton and DeKalb.…”
Section: Discussionsupporting
confidence: 76%
“…The most important factor in influencing the SARS-CoV2 level at 6 months was the peak antibody level following the second vaccination of the primary vaccine regimen. Studies examining the antibody decay kinetics in participants following COVID-19 infection showed that the height of the peak is dependent on disease severity with antibodies for IgG remaining above the positivity threshold for up to 500 days 15–17. Following vaccination our study showed that SARS-CoV2-Ig Ab persistence (≥7.0 U/mL) was 62 days for the AZ and 210 days for the Pfizer vaccine.…”
Section: Discussionmentioning
confidence: 60%
“…Recent research suggests neutralizing and nucleocapsid antibodies to SARS-CoV-2 persist for at least 5-6 months [9][10][11][12] or possibly longer [13], and that re-infection risk is low in the several months after initial infection [14]. This resultant expected reduction in viral spread from these assumptions has inspired the idea of a path to normality.…”
Section: Introductionmentioning
confidence: 99%
“…Reinfection with COVID-19 within a few months is rare [16]; 2. Antibodies from natural infections typically last at least 5 months and cross-reactivity of serological tests is rare [11,12,17,18]; and, 3. Vaccination produces a robust and reasonably long-term antibody response, making it possible to estimate regional seroprevalence as a combination of detection of natural antibodies, and state-level vaccination data [19].…”
Section: Introductionmentioning
confidence: 99%